Pengaruh Kompetensi Mahasiswa Terhadap Kesiapan Memasuki Dunia Kerja Di Era 4.0 - Silvy Putri Wulandari; Pardiman Pardiman; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of student competence on readiness to enter the world of work in the 4.0 era. The sample used in this study was 91 students. The data analysis method used in this research is quantitative data analysis using multiple linear regression analysis. Testing the data used is simultaneous hypothesis testing (F) and partial hypothesis testing (t). The results showed that simultaneously (F test) the variables Knowledge, Attitudes and Skills had a positive and significant effect on Job Readiness and based on the results of a partial test (t test) the Knowledge variable had a positive and significant effect on work readiness, the Attitude variable had a positive and insignificant effect on Job readiness and Skills variables have a positive and significant effect on Job Readiness. Keywords: Knowledge, Attitude, Skills, and Work Readiness